To reduce or to cease: A systematic review and meta-analysis of quantitative studies on self-regulation of driving. (September 2019) - Ang, Boon Hong; Oxley, Jennifer Anne; Chen, Won Sun; Yap, Khai Khun; Song, Keang Peng; Lee, Shaun Wen Huey
Abstract: Introduction : The ability to remain safe behind the wheels can become arduous with aging, yet important for sustaining local travel needs. This review aimed to explore safe mobility issues involving older adults and gain a broad understanding of older drivers' self-regulatory driving practices and motivators behind such behavioral changes, including strategies adopted to reduce or cease driving while maintaining safe mobility. Methods : A systematic literature search was performed on 11 online databases for quantitative studies describing self-regulation of driving amongst older adults aged 60 years and above from database inception until December 2018. Data were described narratively and, where possible, data were pooled using random-effects meta-analysis. Results : Of the 1556 studies identified, 54 studies met the inclusion criteria and 46 studies were included in the meta-analyses. All included studies examined car drivers only. Older adults who were single or female were found to be at higher odds of driving cessation. Physical fitness, mental health, social influence, and support systems received by older adults were important driving forces influencing mobility and adjustments made in their travel patterns. Conclusions : Driving self-regulation amongst older adults is a multifaceted decision, impacting mobility and mental health. Therefore, future interventions and support systems should not only create opportunities for retaining mobility for those who have ceased driving, but also promote better psychological and social well-being for regulators and for those who are transitioning from driving to non-driving status. Practical applications: (a) Engage and educate older adults about self-regulation, including strategies that can be adopted and non-car mobility options available. (b) Expand the research focus to explore potential interactions of factors facilitating or hindering the transition process to develop a more comprehensive framework of self-regulation. (c) Encourage ongoing research to formulate, monitor, and evaluate the effectiveness of policies and interventions implemented. (d) Expand the research horizon to explore and understand the perspectives of older adults from developing countries. Highlights: Older adults who were single or female were more likely to cease driving. Aging can affect the feelings and perceptions of older adults, which were important precursors to adopt and practice self-regulation. Gradual driving reduction was favored over abrupt driving cessation to ensure healthy aging amongst older adults. A research gap in developing countries exists, where mixed travel modes are common and largely involved in road crashes.